Protective effects and structure-activity relationship of oligopeptide AYAPE from Isochrysis Zhanjiangensis on oxidative stress in HUVECs and SH-SY5Y cells - Huijuan Li; Liyuan Li; Yinhuan Mo; Yuan-Lin He; Zhong-Ji Qian (Arabian Journal of Chemistry, 2024)
Oligopeptide (AYAPE, AYP) has been isolated from Isochrysis Zhanjiangensis and it has been proven to have good biological activity potential, but its structural characteristics and structure-activity are not yet very clear. As an oligopeptide of five amino acids, the structural characteristics of AYP are the key factors of its activity. Therefore, through evaluating the antioxidant mechanism and stress degree of AYP in different cells, the active action sites were analyzed to explain the antioxidant structure activity relationship of AYP. The results indicate that under oxidative stress, 50 μM AYP can restore 78.53 % of cell viability. AYP through NF-κB and MAPK signaling pathways inhibit inflammation and cell apoptosis. And then, it activates Nrf2/Keap1 pathway, promotes Nrf2 nuclear transfer, and increases the expression of antioxidant enzymes, thus exerting antioxidant effects. In addition, in order to further explore the structure activity relationship of AYP, quantum mechanics and molecular docking were combined for analysis. The results showed that tyrosine, alanine, proline, and glutamic acid contained in AYP can all contribute to antioxidant activity, and the key amino acids that mainly play an antioxidant role are tyrosine and alanine. Therefore, this study provides a new idea for the rational design of marine oligopeptides based on the activity mechanism in the application of food and health products.